The Role of Community Engagement in Mitigating the Effects of Informal Governance and Enhancing Urban Policy Effectiveness in Contexts of Institutional Weakness in South Asia - Kamaldeen Ibraheem Nageri (International Journal of Social Science and Religion (IJSSR), 2026)
Urban informality and fragmented governance systems continue to shape the landscape of urban development in South Asia, posing challenges to equitable housing, infrastructure access, and inclusive policymaking. This study investigates how informal governance networks, institutional voids, and contested urban spaces interact with formal planning processes, particularly in the context of informal settlements. Using a mixed-methods approach, we draw on document analysis, elite interviews, and process tracing across three South Asian cities, Delhi, Kathmandu, and Dhaka, supplemented by data from 40 planning documents and 25 stakeholder interviews. The analytical framework integrates theories of institutional embeddedness and political informality, with qualitative comparative analysis (QCA) used to identify cross-case patterns. Findings reveal that informal institutions often fill governance voids, but also reinforce uneven power relations and selective legitimacy. Despite state-led efforts at urban upgrading and smart city planning, institutional multiplicity and lack of policy coordination undermine sustainable outcomes. The study recommends more integrated planning frameworks that recognize informal networks as co-governance partners, strengthened community participation, and reforms in inter-agency coordination. These insights offer critical implications for urban policy, especially in achieving the SDGs and inclusive development agendas across the Global South.